Cubic chemically ordered FeRh and FeCo nanomagnets prepared by mass-selected low-energy cluster-beam deposition: a comparative study - Dupuis, Veronique; Robert, Anthony; Hillion, Arnaud; Khadra, Ghassan; Blanc, Nils; Le Roy, Damien; Tournus, Florent; Albin, Clement; Boisron, Olivier; Tamion, Alexandre (Beilstein Journal of Nanotechnology, 2016)
Near the point of equiatomic composition, both FeRh and FeCo bulk alloys exhibit a CsCl-type (B2) chemically ordered phase that is related to specific magnetic properties, namely a metamagnetic anti-ferromagnetic/ferromagnetic transition near room temperature for FeRh and a huge magnetic moment for the FeCo soft alloy. In this paper, we present the magnetic and structural properties of nanoparticles of less than 5 nm diameter embedded in an inert carbon matrix prepared by mass-selected low-energy cluster-beam deposition technique. We obtained a CsCl-type (B2) chemically ordered phase for annealed nanoalloys. Using different experimental measurements, we show how decreasing the size affects the magnetic properties. FeRh nanoparticles keep the ferromagnetic order at low temperature due to surface relaxation affecting the cell parameter. In the case of FeCo clusters, the environment drastically affects the intrinsic properties of this system by reducing the magnetization in comparison to the bulk.
Keywords: bimetallic nanoparticles; magnetic moment and anisotropy; metamagnetic transition